2013
DOI: 10.13066/kspm.2013.8.3.425
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Visual Direction Control on Balance and Gait Speed in Patients with Stroke

Abstract: | Abstract | PURPOSE:The purpose of this study was to examine the effect of visual control on gait speed and balance in patients with stroke. Static balance and gait speed were investigated with comparison and fixed direction of visual. METHODS:We included twenty-six patients with stroke. CONCLUSION:The results from this study showed that the visual direction effected on static balance and the faster visual movement made to increase the gait speed. Therefore the rehabilitation training with visual control may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Eng et al (2008) [46] also reported that curved-path gait training, in which eye and head movements occur first when walking, stimulates the affected side and shifts the body's center of gravity, which can result in segmentation movements. Kwon et al (2013) [47] reported that walking through gazeoriented movements effectively improves gait ability. Based on these findings, patients with stroke require curved-path gait training, which includes changes in direction, as the body center is biased toward the unaffected side, the affected side is neglected, balance becomes difficult, and walking control decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Eng et al (2008) [46] also reported that curved-path gait training, in which eye and head movements occur first when walking, stimulates the affected side and shifts the body's center of gravity, which can result in segmentation movements. Kwon et al (2013) [47] reported that walking through gazeoriented movements effectively improves gait ability. Based on these findings, patients with stroke require curved-path gait training, which includes changes in direction, as the body center is biased toward the unaffected side, the affected side is neglected, balance becomes difficult, and walking control decreases.…”
Section: Discussionmentioning
confidence: 99%